2018
DOI: 10.1037/aca0000186
|View full text |Cite
|
Sign up to set email alerts
|

More than the sum of its parts: Perceiving complexity in painting.

Abstract: To date the complexity of an image is most often equated with its visual complexity. However, recent studies have shown that when it comes to artworks, complexity ratings are also influenced by semantic processes. The present study investigates the relationship between perceived image complexity and content-related processes in paintings by comparing ratings of perceived complexity from experts (art historians) and nonexperts. We show that the processing of the different dimensions of an artwork's content (pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 61 publications
0
20
2
Order By: Relevance
“…While laypersons are positively influenced by increased color saturation, high saturation has a negative influence on experts' evaluations. Also, and in contrast to previous studies (e.g., Kirk et al, 2011;Commare et al, 2018), we show that art experts are less consistent in their aesthetic judgments compared to laypersons. In particular, if they have time to do so, art experts tend to review their initial judgments given after viewing an artwork for a restricted period of time.…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations
“…While laypersons are positively influenced by increased color saturation, high saturation has a negative influence on experts' evaluations. Also, and in contrast to previous studies (e.g., Kirk et al, 2011;Commare et al, 2018), we show that art experts are less consistent in their aesthetic judgments compared to laypersons. In particular, if they have time to do so, art experts tend to review their initial judgments given after viewing an artwork for a restricted period of time.…”
Section: Introductioncontrasting
confidence: 99%
“…At the same time, as suggested above, our results also show that art experts are not quite as consistent in their liking of judgments in very short vs. unrestricted viewing times. This is in contrast to Commare et al (2018), who found that experts exhibit more consistency in complexity judgments than laypersons. Our findings support the claim, predicted by the models of Leder et al (2004) and Pelowski et al (2017), that expertise affects the evaluation of an image, but only at a later (top-down) stage of processing.…”
Section: Effects Of Expertise and Timecontrasting
confidence: 91%
See 2 more Smart Citations
“…Fixation duration on the other hand has been shown to adjust to processing difficulty and to increase with increasing level of complexity in the perception of scenes ( 12 , 13 ). Complexity of artistic images has been described as both a formal characteristic - the amount and variety of represented elements - and a semantic one - whether the iconography of a picture is usual or unusual ( 14 ). An “assembling” gaze is therefore intended as a series of long fixations, aimed at the identification of a subject matter or contextual information.…”
Section: Introductionmentioning
confidence: 99%